2010
DOI: 10.1002/jlcr.1748
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and in vivo evaluation of a F‐18‐labeled pancreatic islet amyloid inhibitor

Abstract: Formation of islet amyloid deposits contributes to the progressive loss of beta‐cells in Type 2 diabetes. Islet amyloid is composed of islet amyloid polypeptide (IAPP). [(N‐Me)G24, (N‐Me)I26]hIAPP(22–27) peptide was found to bind human IAPP with high‐affinity and inhibit fibrillogenesis. We labeled [(N‐Me)G24, (N‐Me)I26]hIAPP(22–27) with fluorine‐18 using N‐succinimidyl‐4‐[18F]fluorobenzoate. Results from biodistribution studies in healthy CF‐1 mice at 1 h p.i. indicated that 18F‐peptide was cleared efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For 18 F-FBA, the biodistribution studies demonstrated that 18 F-FBA had an advantage of rapid clearance in the most tissues. The differences of biodistribution between 18 F-FBA and 18 F-FAC (or 18 F-FPA) could be attributed to the different metabolic pathway, and 18 F-FBA was converted into p - 18 F-fluorohippuric acid derivatives via a glycine-conjugation pathway in the liver and eliminated through the kidneys [ 38 40 ]. Meanwhile, 18 F-FBA PET imaging showed the clear contrast between tumor and inflammation lesion with the highest ratios of tumor-to-inflammation as 1.98 ± 0.15.…”
Section: Discussionmentioning
confidence: 99%
“…For 18 F-FBA, the biodistribution studies demonstrated that 18 F-FBA had an advantage of rapid clearance in the most tissues. The differences of biodistribution between 18 F-FBA and 18 F-FAC (or 18 F-FPA) could be attributed to the different metabolic pathway, and 18 F-FBA was converted into p - 18 F-fluorohippuric acid derivatives via a glycine-conjugation pathway in the liver and eliminated through the kidneys [ 38 40 ]. Meanwhile, 18 F-FBA PET imaging showed the clear contrast between tumor and inflammation lesion with the highest ratios of tumor-to-inflammation as 1.98 ± 0.15.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the major metabolite of 4-18 F-fluorobenzoic acid is excreted rapidly and exclusively in urine as p-18 F-fluorohippurate ( 18 F-PFH) (14). It is known that benzoic acid derivatives are converted in vivo into hippuric acid derivatives via the glycine-conjugation pathway in the liver (15,16).…”
mentioning
confidence: 99%